GLOW : the WILD WONDERS of BIOLUMINESCENCE - Smith, Jennifer N. R. (London : Thames & Hudson Ltd, 2023)
Have you ever wished you had a secret super power? From fungi to fireflies, some living things have a very special talent - they can glow. But are all glowing creatures bioluminescent? Why do they glow, and what can we learn from them? And what is bioluminescence, anyway? Meet the squids that squirts shining mucus at its enemies. Learn how sea-fireflies whizz around spurting bioluminescent goo. Say hello to the scientists who study how and why creatures glow. Get ready to be wowed by the wild wonders of bioluminescence!
t Dinner in the deep -- t Fungal fairy lights -- t The anatomy of bioluminescence -- t The recipe for light -- t A map of bioluminescence.
Includes index.
Keywords: Bioluminescence -- Juvenile literature; Animals -- Juvenile literature; Animal behavior -- Juvenile literature; Plants -- Juvenile literature